Oscillatory Flow Across Plates With Different Shape Of Edges - Mohd Sa'at, Fatimah Al-Zahrah; Cho, Wei Yang (Fakulti Kejuruteraan Mekanikal (FKM), Universiti Teknikal Malaysia Melaka (UTeM), 2016)
Oscillatory flow is the type of flow found in the greener thermoacoustic based technologies.Understanding the behavior of the less understood oscillatory flow of this kind is one of the key feature for the success of the system.Heat exchanger is one of the important part of the system.In this study,oscillatory flow across pile of hot and cold parallel-plates heat exchanger with three different shape of edges (i.e. rectangular,round and triangular shape of edges) were investigated.A suitable computational model was created in ANSYS.The results were compared to theoretical predictions and a good match was found.The study shows that the shape of the edge affects the flow and heat transfer of the system.A triangle-shaped edges with shorter length provides the higher heat transfer between plates and the oscillating fluid compared to plates with round and square edges.The results indicated that the entrance effect could be the reason for the change of heat transfer performance as the shape of edge changes.